2023
DOI: 10.1049/ell2.12851
|View full text |Cite
|
Sign up to set email alerts
|

Volumetric interferometry for sparse 3D synthetic aperture radar with bistatic geometries

Abstract: Synthetic Aperture Radar (SAR) renderings in 3D provide additional target information when compared to 2D by separating out features overlaid in height. However, the required 2D SAR aperture, when Nyquist sampled, necessitates large scanning times that would be impractical for most realistic collections. This research has developed a novel volumetric approach to sparse aperture 3D SAR imaging, which is applicable to bistatic SAR near-field geometries, a generalization of far-field cases. This approach is first… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(9 citation statements)
references
References 13 publications
1
8
0
Order By: Relevance
“…A multistatic SAR geometries extension of the SSARVI approach for generating sub-Nyquist SAR aperture 3D pointcloud renderings [19] was presented. With simulations, it was shown that excessive clustering of trajectories can reduce the sidelobe performance substantially, essentially due to multiple trajectories behaving as a single trajectory.…”
Section: Point-cloud Properties Summary and Polarimetric Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…A multistatic SAR geometries extension of the SSARVI approach for generating sub-Nyquist SAR aperture 3D pointcloud renderings [19] was presented. With simulations, it was shown that excessive clustering of trajectories can reduce the sidelobe performance substantially, essentially due to multiple trajectories behaving as a single trajectory.…”
Section: Point-cloud Properties Summary and Polarimetric Resultsmentioning
confidence: 99%
“…It is a generalisation of the SPCGS algorithm, in this case applicable to multistatic and SAR near-field imaged scenes. Previously the performance of the algorithm was demonstrated for monostatic and bistatic scenarios for a single polarisation channel [19], whereas here it is demonstrated on multistatic collections. It exploits the benefits of volumetric processing, allowing laid over scatterers to be processed and distinguished in a natural manner [20].…”
Section: Bistatic Polarimetric Decompositionmentioning
confidence: 91%
See 2 more Smart Citations
“…We have generalized the SPCGS algorithm into a novel Sparse SAR Volumetric Interferometry (SSARVI) processing-based technique which produces 3D SAR imagery from sparsely sampled SAR aperture data, for bistatic, multistatic and SAR near-field target scenarios 8 . The motivation behind the development was to provide an image formation algorithm suitable for envisaged multistatic SAR collections from satellite constellations and UAV-SAR drone swarms 9,10,11 .…”
Section: Introductionmentioning
confidence: 99%